A salt bath composite nitriding process for high wear-resistant and high fatigue bearing pins
By optimizing the salt bath composition and process parameters, combined with subsequent oxidation treatment and low-temperature tempering steps, a dense nitride layer and a microboride layer are formed, which solves the problems of uneven performance of the nitride layer, limited fatigue performance improvement and insufficient corrosion resistance in traditional salt bath nitride treatment, and significantly improves the comprehensive performance of the shaft pin.
Patent Information
- Application Number
- CN202411851361.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-16
- Publication Date
- 2025-04-04
- Estimated Expiration
- 2044-12-16
AI Technical Summary
Traditional salt bath nitriding treatment has problems such as uneven performance of the nitride layer, limited fatigue performance improvement and insufficient corrosion resistance, which is difficult to meet the needs of high-performance shaft pins.
The optimized salt bath composite nitriding treatment process is adopted to optimize the salt bath composition, dynamic control process parameters and composite post-treatment steps to form a dense nitride layer and microboride layer, improve the bonding strength of the nitride layer and the substrate, and enhance the fatigue and corrosion resistance through oxidation treatment and low-temperature tempering.
The wear resistance, fatigue life and corrosion resistance of the shaft pin are significantly improved, the surface hardness reaches HV800-1100, the nitride layer depth reaches 0.1-0.3mm, the fatigue life is increased by 20%-50%, and the salt spray corrosion resistance time exceeds 600 hours.
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of metal surface treatment, in particular to a method for improving the surface performance of metal parts through salt bath composite nitriding treatment, specifically to a salt bath composite nitriding treatment process for a high wear-resistant and high fatigue shaft pin. Background Art
[0002] The shaft pin is one of the key components in the engine. It is widely used in moving parts such as connecting rods, piston pins, and rocker arms. It needs to withstand large alternating loads and sliding friction. In order to meet the high strength, high efficiency and long life requirements of engine operation, the shaft pin must not only have high wear resistance, but also excellent fatigue resistance. However, traditional surface treatment methods, such as quenching and ordinary nitriding treatment, have been unable to meet the increasingly demanding performance requirements.
[0003] At present, salt bath nitriding, as an effective surface strengthening technology, has achieved certain results in industrial applications. Salt bath nitriding immerses the shaft pin in a molten salt bath containing active nitrogen and carbon source, so that nitrogen atoms and carbon atoms diffuse into the surface of the substrate to form a nitrided layer with high hardness. However, the traditional salt bath nitriding treatment has the following technical limitations:
[0004] 1. Uneven performance of the nitride layer: The traditional formula lacks means to control the composition, resulting in uneven distribution of nitride layer thickness and hardness, which affects the service life of the shaft pin;
[0005] 2. Limited improvement in fatigue performance: The bonding strength between the nitride layer and the substrate is insufficient, and interface cracks are easily formed under high cycle loads;
[0006] 3. Insufficient corrosion resistance: The traditional salt bath process lacks a post-processing stage, and the oxidation resistance of the nitride layer surface is poor.
[0007] With the continuous development of engine technology, the market demand for high-performance axle pins has promoted the technological innovation of nitriding process. In recent years, the introduction of composite salt bath formula and subsequent strengthening treatment has become an important research direction to improve the nitriding effect. Summary of the invention
[0008] In order to solve the above technical problems, the present invention proposes an innovative salt bath composite nitriding treatment process, which significantly improves the wear resistance, fatigue life and corrosion resistance of the axle pin by optimizing the salt bath composition, dynamically controlling the process parameters and composite post-treatment steps.
[0009] In order to achieve the above-mentioned purpose, the present invention adopts the following technical solutions:
[0010] A high wear-resistant and high fatigue axle pin salt bath composite nitriding treatment process, the method comprising the following steps:
[0011] 1) Preprocessing:
[0012] a. Clean the surface of the shaft pin and remove surface impurities by sandblasting or chemical degreasing;
[0013] b. Polish the surface of the shaft pin to a roughness of Ra ≤ 0.8 μm;
[0014] 2) Salt bath composite nitriding treatment:
[0015] a. Nitriding the pin by immersing it in a salt bath containing the following ingredients:
[0016] i. Sodium cyanate 40%-50%, potassium cyanate 10%-20%, sodium carbonate 15%-20%, lithium carbonate 2%-5%;
[0017] ii. Additives: cerium oxide 0.5%-1%, sodium metasilicate 1%-3%, sodium tetraborate 1%-2%, sodium fluoride 0.2%-0.5%;
[0018] b. Keep the temperature at 550-570℃ for 2-4 hours to form a nitride layer;
[0019] 3) Cooling and strengthening treatment:
[0020] a. Slowly cool the nitrided pin to room temperature;
[0021] b. Perform oxidation treatment in an environment of 200-300°C to form a dense oxidation protective layer;
[0022] c. Low temperature tempering at 160-200℃ to release residual stress and improve fatigue resistance;
[0023] Among them, through the synergistic effect of rare earth oxides and fluorides, a dense nitriding layer and a micro-boriding layer are formed, so that the surface hardness of the shaft pin reaches HV800-1100 and the depth of the nitriding layer reaches 0.1-0.3mm.
[0024] The functions of the main components of the salt bath of the present invention are as follows:
[0025] 1. Sodium cyanate (NaCN) 40%-50%: As the main nitrogen source and carbon source, it decomposes and releases active nitrogen atoms and carbon atoms under high temperature conditions; provides sufficient nitriding capacity to form a high-hardness nitrided layer; and improves the efficiency of the nitriding reaction.
[0026] 2. Potassium cyanate (KCN) 10%-20%: Improves the melting characteristics of the salt bath, reduces viscosity, and makes the reaction more uniform; provides an additional source of nitrogen atoms to enhance the density of the nitride layer; reduces the corrosiveness of the salt bath and extends the service life of the equipment.
[0027] 3. Sodium carbonate (Na2CO3) 15%-20%: As an auxiliary stabilizer, it controls the chemical environment of the salt bath to prevent local overheating or component separation; provides stable carbonization conditions, improves the carbon potential distribution of the surface layer; and enhances the wear resistance and fatigue resistance of the nitrided layer.
[0028] 4. Lithium carbonate (Li2CO3) 2%-5%: Improves the fluidity of the salt bath to ensure uniform growth of the nitride layer; improves the diffusion efficiency of carbon atoms to form a denser carbonitride layer; increases the nitridation reaction rate and shortens the process time.
[0029] 5. Cerium oxide (CeO2) 0.5%-1%: Improves the density and hardness of the nitrided layer; enhances the adsorption and diffusion of active nitrogen atoms during the nitriding reaction; reduces surface defects such as the generation of microcracks.
[0030] 6. Lanthanum oxide (La2O3): synergizes with cerium oxide to optimize the microstructure of the nitride layer; improves the fatigue resistance of the nitride layer and reduces interface cracks under high cycle loads.
[0031] 7. Sodium metasilicate (Na2SiO3) 1%-3%: Improve the fluidity of the salt bath to ensure uniform nitriding of the surface of the parts; form a tighter bonding interface between the nitrided layer and the substrate to enhance the bonding strength; control the surface roughness and improve the subsequent performance of the parts.
[0032] 8. Sodium tetraborate (Na2B4O7) 1%-2%: forms a micro-boronated area on the surface of the nitride layer to increase the surface hardness; enhances the wear resistance of the surface and extends the service life of parts; provides additional anti-corrosion protection.
[0033] 9. Sodium fluoride (NaF) 0.2%-0.5%: As an activator, it enhances the nitriding reaction rate and shortens the processing time; reduces the microcracks generated during the nitriding process, optimizes the surface integrity; and improves the bonding strength between the nitriding layer and the substrate.
[0034] The advantages of the synergistic effect of the above components are as follows:
[0035] 1. Sodium cyanate and potassium cyanate provide an efficient nitriding environment, rare earth oxides and sodium metasilicate improve the layer structure, and sodium fluoride and sodium tetraborate enhance the surface performance. 2. Lithium carbonate and sodium metasilicate improve fluidity, ensure uniform reaction, and reduce energy consumption. 3. By adding rare earth oxides and fluorides, the wear resistance, hardness and fatigue resistance of the nitriding layer are significantly improved. This multi-component salt bath formula solves the problems of uneven performance and insufficient fatigue life of the traditional salt bath nitriding layer through precise control, providing reliable guarantee for the manufacture of high-performance shaft pins.
[0036] Preferably, the rare earth oxide in the salt bath also includes a mixture of lanthanum oxide, wherein the mass ratio of cerium oxide to lanthanum oxide is (1.5-2):1.
[0037] Preferably, the amount of sodium fluoride added to the salt bath is 0.3%-0.4%, and the nitriding reaction rate is enhanced by regulating the fluoride ion concentration, while reducing the generation of microcracks on the substrate surface.
[0038] Preferably, the mass ratio of sodium metasilicate to lithium carbonate added to the salt bath is (3-4):1, so as to optimize the fluidity of the salt bath and enhance the interface bonding strength between the nitride layer and the substrate.
[0039] Preferably, 2% to 3% potassium borate is added to the salt bath to form a micro-borated area outside the nitrided layer during the nitriding process.
[0040] Preferably, during the salt bath treatment, the salt bath temperature is dynamically controlled and the temperature is gradually reduced to 500° C. at a cooling rate of 0.5° C. / min in the later stage of the treatment to improve the hardness gradient distribution of the nitride layer.
[0041] Preferably, the environment of the oxidation treatment stage is oxygen-rich humid air with an oxygen concentration of 25%-30%, and the humidity is controlled to be 30%-40% to form a uniform and dense Fe3O4 protective layer; and / or, vibration auxiliary treatment is added in the low-temperature tempering stage to release stress at a vibration frequency of 50-100 Hz, further reducing the residual stress of the substrate and improving fatigue life.
[0042] Preferably, micro plasma etching technology is used in the pretreatment stage to remove surface impurities and form a nanoscale activation layer on the surface to enhance the diffusion efficiency of nitrogen atoms; and / or, an external electromagnetic field is applied during the nitridation process with a frequency of 20-50 Hz to increase the penetration depth of the nitridation layer and reduce the nitridation time.
[0043] Preferably, the shaft pin material is 40CrNiMo or 42CrMo4 alloy steel.
[0044] Furthermore, the present invention also discloses a high wear-resistant and high fatigue shaft pin obtained by the processing technology.
[0045] The present invention adopts the above-mentioned technical solution, adopts an innovative salt bath formula and dynamic process control, and combines subsequent oxidation treatment and low-temperature tempering strengthening steps to significantly improve the comprehensive performance of the shaft pin. The technical effects of the present invention are specifically embodied as follows:
[0046] 1. Significant improvement in surface hardness: By optimizing the salt bath composition (including sodium cyanate, potassium cyanate, lithium carbonate and rare earth oxides, etc.), a dense nitriding layer and a micro-boronization layer are formed during the nitriding process, so that the surface hardness of the shaft pin reaches HV800-1100, which effectively improves the wear resistance and extends the service life of the parts.
[0047] 2. Improved uniformity of nitriding layer performance: Dynamic temperature control (at a cooling rate of 0.5°C / min) and a combination of sodium metasilicate and lithium carbonate are used to optimize the fluidity of the salt bath, making the nitriding layer thickness uniform and more densely distributed, and the depth of the nitriding layer can reach 0.1-0.3 mm.
[0048] 3. Significantly enhanced fatigue resistance: Through the synergistic effect of rare earth oxides (cerium oxide, lanthanum oxide) and sodium fluoride, the bonding strength between the nitride layer and the substrate is improved, reducing the formation of interface cracks under high cycle loads; at the same time, combined with vibration-assisted low-temperature tempering treatment, residual stress is effectively released, so that fatigue resistance is improved by 20%-50%.
[0049] 4. Significantly improved corrosion resistance: After nitriding, oxidation treatment is added in an oxygen-rich humid air environment to form a uniform and dense Fe3O4 protective layer, which greatly improves the corrosion resistance of the axle pin in harsh environments such as high temperature and high humidity.
[0050] 5. Improved process efficiency and environmental performance: The composite salt bath formula and external electromagnetic field assisted process are used to accelerate the nitriding reaction rate, reduce energy consumption and processing time (shortened by 10%-20%); at the same time, the salt bath composition is optimized, the use of traditional highly toxic ingredients is reduced, and the impact on the environment is reduced.
[0051] In summary, the present invention significantly improves the wear resistance, fatigue resistance and corrosion resistance of the shaft pin, and provides an efficient, economical and environmentally friendly surface strengthening solution for the manufacture of high-performance mechanical parts. The process of the present invention is not only applicable to engine shaft pins, but can also be extended to other mechanical parts that require high wear resistance and high fatigue performance, such as connecting rod pins, piston pins, gear shafts and high-strength moving parts, to meet the needs of various industrial fields. DETAILED DESCRIPTION
[0052] The following is a clear and complete description of the technical solutions in the embodiments of the present invention in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0053] Example 1
[0054] 1. Pretreatment: Sandblast clean the 42CrMo4 alloy steel shaft pin; polish to a surface roughness of Ra ≤ 0.8μm.
[0055] 2. Salt bath nitriding:
[0056] Salt Bath Recipe:
[0057] Sodium cyanate (NaCN): 45%
[0058] Potassium cyanate (KCN): 15%
[0059] Sodium carbonate (Na2CO3): 18%
[0060] Lithium carbonate (Li2CO3): 3%
[0061] additive:
[0062] Cerium oxide (CeO2): 0.8%
[0063] Lanthanum oxide (La2O3): 0.4%
[0064] Sodium metasilicate (Na2SiO3): 2%
[0065] Sodium tetraborate (Na2B4O7): 1.5%
[0066] Sodium fluoride (NaF): 0.3%
[0067] Nitriding temperature: 560°C; holding time: 3 hours.
[0068] 3. Cooling and post-processing:
[0069] 1) Slowly air cool to room temperature;
[0070] 2) Oxidation treatment in an oxygen-rich wet air environment at 250°C for 20 minutes;
[0071] 3) Perform low temperature tempering at 180°C and 60 Hz vibration frequency for 1 hour.
[0072] Example 2
[0073] Preprocessing:
[0074] Same as Example 1.
[0075] Salt bath nitriding: the salt bath formula is the same as that in Example 1;
[0076] During the nitriding process, a 20 Hz electromagnetic field was applied to enhance the diffusion of nitrogen atoms; the nitriding temperature was 560°C; and the holding time was 3 hours.
[0077] Cooling and post-treatment: same as Example 1.
[0078] Example 3
[0079] Pretreatment: Same as Example 1.
[0080] Salt bath nitriding: the salt bath formula is the same as that in Example 1;
[0081] Nitriding temperature: 560°C; Dynamic temperature control: After nitriding, cool to 500°C at a rate of 0.5°C / min, and then cool naturally to room temperature.
[0082] Cooling and post-treatment: The oxidation treatment and low-temperature tempering are the same as those in Example 1.
[0083] Comparative Example 1
[0084] Pretreatment: Same as Example 1.
[0085] Salt bath nitriding:
[0086] Salt Bath Recipe:
[0087] Sodium cyanate (NaCN): 50%
[0088] Potassium cyanate (KCN): 20%
[0089] Sodium carbonate (Na2CO3): 30%
[0090] No additives;
[0091] Nitriding temperature: 560℃;
[0092] Keep warm time: 3 hours.
[0093] Cooling and post-treatment: same as Example 1.
[0094] Comparative Example 2
[0095] Pretreatment: Same as Example 1.
[0096] Salt bath nitriding:
[0097] Salt Bath Recipe:
[0098] Sodium cyanate (NaCN): 45%
[0099] Potassium cyanate (KCN): 15%
[0100] Sodium carbonate (Na2CO3): 18%
[0101] Lithium carbonate (Li2CO3): 3%
[0102] additive:
[0103] Cerium oxide (CeO2): 0.8%
[0104] Sodium metasilicate (Na2SiO3): 2%
[0105] Sodium tetraborate (Na2B4O7): 1.5%
[0106] Nitriding temperature: 560℃;
[0107] Keep warm time: 3 hours.
[0108] Cooling and post-treatment: same as Example 1.
[0109] Comparison of test items and results
[0110] 1. Test method:
[0111] Surface hardness: Surface hardness is measured using a microhardness tester.
[0112] Nitride layer thickness: measured by metallographic microscope.
[0113] Fatigue performance: high cycle fatigue test (frequency 50Hz).
[0114] Wear resistance: Friction and wear tests measure the amount of wear.
[0115] Corrosion resistance: Salt spray test to test the corrosion resistance time.
[0116] 2. Test results:
[0117] Test items Example 1 Example 2 Example 3 Comparative Example 1 Comparative Example 2 Surface hardness (HV) 1050 1080 1065 780 920 Nitriding layer thickness (mm) 0.28 0.30 0.29 0.15 0.22 High cycle fatigue life (10,000 times) 150 160 155 80 110 Wear amount (mg) 12 10 11 28 18 Salt spray corrosion resistance time (h) 600 620 610 300 450
[0118] Result analysis:
[0119] 1. Surface hardness and nitride layer thickness:
[0120] Examples 1-3 are significantly higher than the comparative example, especially Example 2, which has the best performance with a hardness of HV1080 and a nitride layer thickness of 0.30 mm under the assistance of an electromagnetic field.
[0121] 2. Fatigue performance:
[0122] The embodiments all significantly improve fatigue life, and in embodiment 2, the fatigue life is increased to 1.6 million times due to enhanced diffusion of electromagnetic field.
[0123] 3. Wear resistance:
[0124] The wear loss of the examples was significantly reduced, and Example 2 was the best (10 mg), indicating that the hardness of the micro-boronized area and the surface layer significantly improved the wear resistance.
[0125] 4. Corrosion resistance:
[0126] The oxidation treatment in the examples formed a dense protective layer, and the salt spray corrosion resistance time exceeded 600 hours, which was significantly improved compared with the comparative example.
[0127] The above is a description of the embodiments of the present invention. Through the above description of the disclosed embodiments, professionals and technicians in the field can implement or use the present invention. Various modifications to these embodiments will be apparent to professionals and technicians in the field. The general principles defined herein can be implemented in other embodiments without departing from the spirit or scope of the present invention. Therefore, the present invention will not be limited to these embodiments shown in this article, but will conform to the widest range consistent with the principles and novelties disclosed herein.
Claims
1. A high wear-resistant and high fatigue axle pin salt bath composite nitriding treatment process, characterized in that: The treatment process includes the following steps: 1) Preprocessing: a. Clean the surface of the shaft pin and remove surface impurities by sandblasting or chemical degreasing; b. Polish the surface of the shaft pin to a roughness of Ra ≤ 0.8 μm; 2) Salt bath composite nitriding treatment: a. Immerse the shaft pin in a salt bath containing the following ingredients for nitriding: i. Sodium cyanate 40%-50%, potassium cyanate 10%-20%, sodium carbonate 15%-20%, lithium carbonate 2%-5%; ii. Additives: cerium oxide 0.5%-1%, sodium metasilicate 1%-3%, sodium tetraborate 1%-2%, sodium fluoride 0.2%-0.5%; b. Keep warm at 550-570°C for 2-4 hours to form a nitrided layer; 3) Cooling and strengthening treatment: a. Slowly cool the nitrided pin to room temperature; b. Perform oxidation treatment in a 200-300°C environment to form a dense oxide protective layer; c. Perform low temperature tempering at 160-200°C to release residual stress and improve fatigue resistance; The shaft pin material is 40CrNiMo or 42CrMo4 alloy steel; the mass ratio of sodium metasilicate and lithium carbonate added in the salt bath is (3-4):1, so as to optimize the fluidity of the salt bath and enhance the interface bonding strength between the nitriding layer and the substrate; 2%-3% potassium borate is also added to the salt bath to form a micro-borated area outside the nitriding layer during the nitriding process; through the synergistic effect of rare earth oxides and fluorides, a dense nitriding layer and a micro-borated layer are formed, so that the surface hardness of the shaft pin reaches HV800-1100, and the depth of the nitriding layer reaches 0.1-0.3mm.
2. The treatment process according to claim 1, characterized in that: The rare earth oxides in the salt bath also include a mixture of lanthanum oxide, wherein the mass ratio of cerium oxide to lanthanum oxide is (1.5-2):
1.
3. The treatment process according to claim 1, characterized in that: The amount of sodium fluoride added to the salt bath is 0.3%-0.4%. The nitriding reaction rate is enhanced by adjusting the fluoride ion concentration, while reducing the generation of microcracks on the substrate surface.
4. The treatment process according to claim 1, characterized in that: During the salt bath treatment, the salt bath temperature was dynamically controlled and gradually reduced to 500°C at a cooling rate of 0.5°C / min in the later stage of the treatment to improve the hardness gradient distribution of the nitride layer.
5. The treatment process according to claim 1, characterized in that: The environment of the oxidation treatment stage is oxygen-rich humid air with an oxygen concentration of 25%-30%, and the humidity is controlled at 30%-40% to form a uniform and dense Fe3O4 protective layer; and / or, vibration auxiliary treatment is added in the low-temperature tempering stage to release stress at a vibration frequency of 50-100 Hz, further reducing the residual stress of the substrate and improving fatigue life.
6. The treatment process according to claim 1, characterized in that: In the pretreatment stage, micro plasma etching technology is used to remove surface impurities and form a nanoscale activation layer on the surface to enhance the diffusion efficiency of nitrogen atoms; and / or, an external electromagnetic field is applied during the nitridation process with a frequency of 20-50 Hz to increase the penetration depth of the nitridation layer and reduce the nitridation time.
7. A high wear-resistant and high fatigue bearing pin obtained by the treatment process described in any one of claims 1 to 6.
Citation Information
Patent Citations
Positioning shaft pin QPQ heat treatment method
CN110983238A
Heat treatment process of high-carbon chromium bearing part
CN114427074A
Metal surface hardening method
CN114836711A